Standardised material properties for numerical parametric studies of stainless steel structures and buckling curves for tubular columns - Afshan, Sheida (2020)
While the nominal material properties given in material specifications are suitable for design purposes, for the generation of realistic numerical parametric results that are ‘equivalent’ to physical experiments, material properties that are representative of actual structural members are required. Standardised values for these properties are proposed herein. Following analysis of a comprehensive database of material test data from different stainless steel products, values for the yield stress fy, the ultimate tensile stress fu, the strain at ultimate tensile stress εu and the Ramberg-Osgood parameters n and m are proposed. This enables the generation of standardised stress-strain curves for typical austenitic, duplex and ferritic stainless steel sections. Following this, an extensive numerical modelling study, incorporating the proposed standardised material parameters, was carried out to investigate the effect of production route (cold-formed and hot-finished) and material grade (austenitic, duplex and ferritic) on the flexural buckling behaviour and design of stainless steel square, rectangular and circular hollow section compression members. The FE generated flexural buckling data, combined with column test data from the literature, were used to derive a series of buckling curves for the design of stainless steel compression members. The suitability of the proposals was confirmed by means of reliability analysis.